Ependymal cyst of the spinal cord: case report - Wisoff, Hugh S. (1971)
A subarachnoid ependymal cyst of the spinal cord is rarely reported. A 44 year old man with a cyst compressing the lower spinal cord and conus medullaris is described. Excellent functional recovery followed excision of the lesion. The cells lining the cyst were histologically indistinguishable from normal ependymal cells, but, unlike the normal ependymal cells which are related to subependymal glial tissue, the cells lining the cyst abutted directly on the connective tissue forming the cyst wall. This is in contrast with ependymal lined cysts occurring within the conus medullaris, and intradural teratomatous cysts which consistently contain intracytoplasmic mucinous material. It is postulated that an ependymal cyst could result from isolation of ependymal cells from either the roof or floor plates during embryogenesis of the neural tube.